Toward a better understanding of the language conducive context: an ecological perspective on children's progress in the second language in bilingual preschool. Issue 4 (21st April 2021) - Schwartz, Mila; Deeb, Inas
ABSTRACT: Van Lier's [2004. The Ecology and Semiotics of Language Learning: A Sociocultural Perspective . Boston: Kluwer Academy] concept of ecology of language learning is applicable to our focus on children's active engagement in bilingual preschool classroom activities, which are conducive to language learning. The aim of this study was to explore the nature of relationships between these activities and phases in L2 progress and to identify the activities that are conducive to productive L2 use in the bilingual Hebrew–Arabic-speaking preschool classroom in Israel. During one academic year, we applied a mixed methods design, combining quantitative and qualitative ethnographic approaches to data collection and analysis. The credibility of the weekly field notes and video-recorded observations was enhanced by semi-structured interviews with the teachers. We took a close look at six 3-year-old children – three L1 Arabic-speaking children and three L1 Hebrew-speaking children. The analysis revealed that, during all classroom activities, the children demonstrated diverse developmental phases. The phases' frequency of occurrence differed from activity to activity. The teacher-led activities were characterized mostly by receptive bilingual knowledge and telegraphic and formulaic speech, with few cases of L2 production. At the same time, the child-led activities were the most conducive to the children's initiation of productive L2 use.